A comparative study on the diagnostic utility of ultrasonography with conventional radiography and computed tomography scan in detection of zygomatic arch and mandibular fractures - Koijam Sashikumar Singh; S Jayachandran (Wolters Kluwer Medknow Publications, 2014)
Objectives: The objective of the following study is to evaluate the usefulness of ultrasonography (USG) in comparison with conventional radiography and computed tomography (CT) scan in the diagnosis of zygomatic arch and mandibular fractures. Materials and Methods: A total of 40 patients with suspected fracture of the zygomatic arch and/or mandibular fractures were included in the study. Two groups (one for zygomatic arch fractures and the other for mandibular fractures) of 20 patients each were designed for the study. Ultrasonographic examinations were performed using small linear probe (LA435, Siemens Acuson Antares) with 10 MHz frequency. Data from CT and conventional radiography were compared with that of USG. Results: Sensitivity and specificity of USG in assessing zygomatic arch fractures were 100% and 100%, respectively; and that of mandibular fractures were 94.74% and 100%, respectively. Overall sensitivity, specificity, positive predictive value, and negative predictive value of USG against CT in diagnosing zygomatic arch and mandibular fractures were found out to be 97.4%, 100%, 100%, and 66.7%, respectively. Conclusion: USG is a very reliable tool in detection of fractures involving zygomatic arch and mandible. It can be used for screening of suspected fractures of zygomatic arch and mandible to avoid unnecessary radiation exposure from conventional radiography and CT scans.